PENERAPAN METODE OVERMODULASI UNTUK MENAMBAH JANGKAUAN KECEPATAN PERMANENT MAGNET SYNCHRONOUS MOTOR (PMSM) - Amiruddin, M. Fero; Djuriatno, Waru; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
The Permanent Magnet Synchronous Motor (PMSM) is a type of electric motor frequently used in electric vehicles due to its reliability and efficiency. However, electric vehicles have a maximum speed limit caused by the Back Electromotive Force (BEMF), which prevents further torque generation. The Overmodulation method is chosen to enhance the maximum speed of PMSMs. Byemploying overmodulation, the inverter output voltage will be higher than using ordinary SVPWM. This voltage increase allows the current to flow for a longer duration, generating torque and thus extending the speed range of the PMSM. This study utilized the PLECS software for simulation. The results revealed a 13.7% increase in RMS voltage, a 40.7% increase in current, higher power output, a 1.08% increase in speed range, and a 1007% increase in electrical torque. Overmodulation enhances voltage, current, power, and speed range without altering the components. Keywords: SVPWM, Overmodulation, BEMF, Motor Speed, PLECS